MANAJEMEN PERENCANAAN PESERTA DIDIK DI SMPIQU AL-BAHJAH CIREBON - Fizrih, Gina Mukti; Ghadisti, Manggi Meiyolly; Fatonaro, Putri Muawaliyah (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2023)
This research was conducted at SMPIQu Al-Bahjah Cirebon with the aim of describing the management of student planning that it implements. The research method used was qualitative with data collection techniques through interviews, observation, and documentation. The results of the study found that the management of learner planning carried out starts from analyzing the needs of students based on the number of registrants in the previous year, planning learner recruitment by forming a committee and disseminating information with a formal approach, selection planning which is carried out by involving religious exams and reading the Qur'an and involving the boarding school, orientation planning which is carried out jointly by introducing the school environment and boarding school, different placement planning between class VII and classes VIII and IX, as well as recording and reporting using a master book, attendance, and student achievement records. Learner planning management at SMPIQu Al-Bahjah is ideal according to existing theories and regulations and in several stages of learner planning, pesantren characteristics are inserted.